2019
DOI: 10.1016/j.biocon.2019.06.031
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal selection of key resources by cattle in a mixed savannah-wetland ecosystem increases the potential for conflict with lions

Abstract: In Africa's pastoral conservation landscapes, apex predators frequently kill livestock. Retaliatory persecution such as poisoning threatens predators, but also non-target biota. Several factors influence conflict severity, including livestock husbandry, overlap in seasonal habitat use, and the degree to which livestock perceive and are able to respond to a landscape of fear. We investigated these factors by GPS-tracking 42 Tswana beef cattle (Bos taurus) from 29 herds in 2017 and six lions (Panthera leo) from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…They are also less likely to cause injuries to attacking lions, and so may be the easiest of targets and increasingly preferred by lions, especially during panicked herd stampedes resulting from enclosure attacks when, contrary to predation on free-ranging herds, lions exhibited a clear preference for inexperienced calves. Weise et al [6] demonstrated that cattle in the study area do not exhibit a pronounced fear in response to lion presence and predation. Instead, cattle utilise different habitat types according to their seasonal resource needs, mimicking the resource utilisation patterns of buffalo [53], thereby increasing predation risk significantly [6].…”
Section: Discussionmentioning
confidence: 83%
See 4 more Smart Citations
“…They are also less likely to cause injuries to attacking lions, and so may be the easiest of targets and increasingly preferred by lions, especially during panicked herd stampedes resulting from enclosure attacks when, contrary to predation on free-ranging herds, lions exhibited a clear preference for inexperienced calves. Weise et al [6] demonstrated that cattle in the study area do not exhibit a pronounced fear in response to lion presence and predation. Instead, cattle utilise different habitat types according to their seasonal resource needs, mimicking the resource utilisation patterns of buffalo [53], thereby increasing predation risk significantly [6].…”
Section: Discussionmentioning
confidence: 83%
“…Weise et al [6] demonstrated that cattle in the study area do not exhibit a pronounced fear in response to lion presence and predation. Instead, cattle utilise different habitat types according to their seasonal resource needs, mimicking the resource utilisation patterns of buffalo [53], thereby increasing predation risk significantly [6].…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations